Arranging Haulage for Florida's Produce - Richard Beilock (EDIS)
Over 99% of interstate shipments of Florida produce are by truck. Motor carriers do not magically know when there is a potential load they would find attractive. Rather, motor carriers and shipper/receivers must locate one another and negotiate terms, either directly or through an intermediary. This report will examine the methods used to arrange produce haulage and changes over the past two decades. This is EDIS document, FE540, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.